2010
DOI: 10.1111/j.1442-9993.2010.02221.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment limitation in dry sclerophyll forests: Regeneration requirements and potential density-dependent effects in Eucalyptus tricarpa (L.A.S. Johnson) L.A.S. Johnson & K.D. Hill (Myrtaceae)

Abstract: Recruitment limitation in canopy trees is receiving increasing attention as restoration of tree cover for connectivity, biodiversity offsets, carbon-trading and improved catchment health becomes more prominent. Recruitment limitation is often addressed by examining seed traits and germination requirements. Distance between trees is also often explored as a factor, particularly in agricultural landscapes where forest structure has been altered, with large distances between fragments generating Allee effects lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Our results highlight that these two species are vulnerable to climate change as they may be unable to regenerate in the areas investigated in this study. Our outcomes for E. tricarpa are supported by Orscheg et al (2011) who found that recruitment of E. tricarpa is restricted and climate change may have adverse effects on its germination. The rapid decline in establishment potential for E. tricarpa is also supported by Byrne et al (2013) who found that the species can only perform well under a narrow range of conditions and Newell et al (2009) who predicted that the distribution of E. tricarpa may decline under climate change and that the species may be lost from most of its current distribution.…”
Section: Climate Change Germination Timing Shift Establishment and Species Potential Risksupporting
confidence: 81%
See 1 more Smart Citation
“…Our results highlight that these two species are vulnerable to climate change as they may be unable to regenerate in the areas investigated in this study. Our outcomes for E. tricarpa are supported by Orscheg et al (2011) who found that recruitment of E. tricarpa is restricted and climate change may have adverse effects on its germination. The rapid decline in establishment potential for E. tricarpa is also supported by Byrne et al (2013) who found that the species can only perform well under a narrow range of conditions and Newell et al (2009) who predicted that the distribution of E. tricarpa may decline under climate change and that the species may be lost from most of its current distribution.…”
Section: Climate Change Germination Timing Shift Establishment and Species Potential Risksupporting
confidence: 81%
“…Six Eucalyptus species were selected from dry and wet sclerophyll forest types located in the temperate region of Victoria, south-eastern Australia. The co-occurring Symphyomyrtus (subgenera) species E. microcarpa (grey box), E. polyanthemos (red box) and E. tricarpa (red ironbark) represent the dry open 'box-ironbark' of the warm temperate region of Victoria (Newman 1961;Orscheg et al 2011). Annual rainfall in this region ranges from 400 to 1000 mm and the average monthly maximum/minimum temperature range from 23 to 33 °C/ -1 to 7 °C, respectively (Boland et al 2006).…”
Section: Species Selectionmentioning
confidence: 99%
“…The co‐occurring species E. microcarpa (grey box), E. polyanthemos (red box) and E. tricarpa (red ironbark) represent the dry open forests of the warm temperate region of Victoria (Newman ; Orscheg et al . ). Annual rainfall in this region ranges from 400 to 970 mm and the maximum/minimum temperature range from 23°C to 33°C/−1°C to 4°C (Boland et al .…”
Section: Methodsmentioning
confidence: 97%
“…Six Eucalyptus species were selected from both dry and wet sclerophyll forest types located in the temperate region of Victoria, south-east Australia. The co-occurring species E. microcarpa (grey box), E. polyanthemos (red box) and E. tricarpa (red ironbark) represent the dry open "box-ironbark" sclerophyll forest of the warm temperate region of Victoria (Newman 1961;Orscheg et al 2011). Annual rainfall in this region ranges from 400 to 970 mm and the maximum/minimum temperature ranges from 23 to 33°C / -1 to 4°C respectively (Boland et al 2006).…”
Section: Species Selectionmentioning
confidence: 99%
“…Growth of E. tricarpa may benefit under a defined range of temperature increase but if drier conditions arise then the species may be outcompeted by E. polyanthemos. The recruitment of E. tricarpa in Victorian "box ironbark" forests has recently been found to be highly restricted (Orscheg et al 2011). Combining this with the species limited growth under increasing temperatures, decreased moisture availability and lower air humidity(all predicted to occur due to climate change), suggests that E. tricarpa is at risk of being out competed by its current co-occurring species due to their divergent growth phenologies.…”
Section: Future Climate and Species Vulnerabilitymentioning
confidence: 99%